An Analysis of current practice of feeding animals and its alternatives - Dr. Muhammad Abdullah (jihat-ul-islam, 2020)
There is a transaction among the people in our society which called Adhea. Its process is that a people give his animal to another for bringing up. Then the second person perform his duty and after some years when this animal becomes adult or born a child, then the owner him this child to second person or sell this animal and profit divides between them. This transaction is not according to the Islamic rules. So the wages and time period of work are not fixed. There are some other alternate situations to solve the problem of this issue. If we manage our transaction according to that we can act upon the Fiqe Hanafi. This is a current issue of our age we can change our transactions according to these opinions which is in the light of islamic rules and regulation.